STEAM Oriented Science Learning Management During The COVID-19 Pandemic - Mimin Vera Dwi Priyantini; Bambang Sumardjoko; Choiriyah Widyasari; Yulia Maftuhah Hidayati (Universitas Muhammadiyah Surakarta, 2021)
This research is motivated by the importance of experimentation in science learning which cannot be done directly in online learning during the pandemic. The application of STEAM is one solution to problems that arise in the management of science learning in elementary schools during the pandemic. The subjects of this study were 20 grade 6 students in an elementary school in Surakarta. The method used in this study was descriptive qualitative with a case study design. The recruited informants consisted of students and their parents. The techniques used in this research are interviews, observation and documentation. Data analysis using data collection techniques, data reduction, presentation of power and drawing conclusions. The data validity technique is technique triangulation and source triangulation. The results of this study indicate that (1) the application of online learning changes the way students learn (2) In online learning experiments cannot be done directly (3) During the pandemic, teachers are required to innovate in the teaching and learning process (4) The STEAM approach can provide a meaningful experience for students (5) STEAM can encourage student development for the better. The implications of this research are: First, more and more teachers are implementing the STEAM approach in the teaching and learning process as an alternative so that students can learn optimally. Both parents are willing to take the time to observe and assist their daughter's online learning process. This study describes the application of the STEAM approach in online learning during a pandemic